Self-assembled multi-epitope peptide amphiphiles enhance the immune response against enterovirus 71 - Kim, Yu Gyeong; Lee, Yunsu; Kim, Joo Hee; Chang, Sun Young; Jung, Jong Wha; Chung, Woo Jae; Jin, Hyo Eon (Nanomaterials, 2020)
Subunit vaccines consist of non-genetic material, such as peptides or proteins. They are considered safe because they have fewer side effects; however, they have low immunogenicity when used alone. We aimed to enhance the immune response of peptide-based vaccines by using self-assembled multimeric peptide amphiphiles (PAs). We designed two epitope PAs by conjugating epitope peptides from Enterovirus 71 (EV71) virus particle (VP) 1 and VP3 capsid proteins with different fatty acid chain lengths (VP1PA and VP3PA). These PAs self-assembled into supramolecular structures at a physiological pH, and the resulting structures were characterized using atomic force microscopy. Multi-epitope PAs (m-PAs) consisted of a 1:1 mixture of VP1PA and VP3PA solutions. To evaluate immunogenicity, m-PA constructs were injected with adjuvant subcutaneously into female Balb/c mice. Levels of antigen-specific immunoglobulin G (IgG) and IgG1 in m-PA-injected mice serum samples were analyzed using ELISA and Western blotting. Additionally, cytokine production stimulated by each antigen was measured in splenocytes cultured from immunized mice groups. We found that m-PA showed improved humoral and cellular immune responses compared to the control and peptide groups. The sera from m-PA immunized mice group could neutralize EV71 infection and protect host cells. Thus, self-assembled m-PAs can promote a protective immune response and can be developed as a potential platform technology to produce peptide vaccines against infectious viral diseases.
Keywords: Enterovirus 71; Immune stimulator; Peptide amphiphile; Vaccine; Viral infectious disease